Investigating Teachers' Strategies in Applying Online Teaching Platforms to Teach English during Covid-19 Pandemic - Fitria Saqinah Damayanti; Sudarsono Sudarsono; Sugeng Ariyanto (English Education Study Program, 2022)
Abstract In early 2020, face-to-face learning has been shifted to online learning caused by the Covid-19 pandemic. Therefore, this study was conducted to examine the online teaching platform used by English teachers and their strategies to attract students' active participation. The researcher chose a case study as the research design. Meanwhile, the data were collected by interviewing four English teachers and validated by conducting interviews with four students from each teacher and observing the online class activities. Then, the data collected was analyzed using the theory of Miles and Huberman (1994). The result showed applications that teachers used to teach online classes. In addition, they had some teaching strategies that focused more on how the teacher attracted the students to participate in the class actively. However, teachers still needed to develop teaching strategies that focus on the active participation of students and their learning goals. Keywords: Online teaching platforms, teaching strategies, online learning.